Hubungan Pola Makan Dan Aktivitas Fisik Dengan Penyakit Jantung Koroner Di Rsud Labuang Baji Makassar - Pashar, Imran; Sultan; Linda Wendikbo (PT. Pubsains Nur Cendekia, 2024)
The heart is a human organ that has a vital function in the human body. Coronary heart disease can cause the heart's function to decrease, causing blood to flow throughout the body to be disrupted or the heart to fail to distribute blood throughout the body. To find out the relationship between diet and physical activity with coronary heart disease at Labuang Baji Regional Hospital. The research uses quantitative methods using survey methods. The sample from this research was 76 CHD respondents. Sampling uses probability sampling techniques. Data analysis used univariate and bivariate analysis, while data collection used a research measuring tool in the form of a dietary pattern questionnaire with a total of 12 question items. The results obtained for good eating patterns were 65 respondents (85.6%) and bad eating patterns were obtained by 11 respondents (14.4%). Low physical activity was 9 respondents (11.9%), high physical activity was 67 respondents (88.1%). It can be seen that eating patterns and physical activity obtained a value of p = 0.000 (p < 0.05). Most of the respondents' eating patterns were good (85.6%). Physical activity Most respondents have high physical activity (77.6%). There is a relationship between eating patterns and physical activity for CHD at Labuang Baji Regional Hospital, Makassar (p value = 0.107 < 0.005)